Evaluating the relevance, credibility and legitimacy of a novel participatory online tool - Maria Juschten; Ines Omann (Environmental Science & Policy, 2023)

Assessing opportunities for scaling out, up and deep of win-win solutions for a sustainable world - Ines Omann; Moritz Kammerlander; Jill Jäger; Alexander Bisaro; J. David Tàbara (Climatic Change, 2020)

Scenarios for investigating risks to biodiversity - Joachim H. Spangenberg; Alberte Bondeau; Timothy R. Carter; Stefan Fronzek; Jill Jaeger; Kirsti Jylhä; Ingolf Kühn; Ines Omann; Alex Paul; Isabelle Reginster; Mark Rounsevell; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2012)
Aim This paper describes a set of integrative scenarios developed in the ALARM (Assessing LArge‐scale environmental Risks for biodiversity with tested Methods) project. The ultimate aim of ALARM was to develop and test methods and protocols for the assessment of large‐scale environmental risks to biodiversity and to evaluate mitigation options. Scenarios provide a tool for exploring such risks and the policy options to mitigate them; therefore they play a central role within the ALARM project. Methods Three integrative scenarios (liberalization, business as might be usual, sustainability) were developed and illustrated using the econometric model described in a subsequent paper. They are contextualized with projections from climate models and provide the input for model‐based assessments of biodiversity trends. Additionally, three shock scenarios were developed (Gulf Stream collapse, peak oil, pandemic) to demonstrate the limits of linear extrapolation. As these extend beyond model capabilities, they are discussed semi‐quantitatively based on modelling insights. Results Although the policy impacts on biodiversity are different for different pressures, biomes and species groups, some general trends could be identified. An extension of current EU policies will act as a brake on current trends by slowing down the loss of biodiversity in many cases and in most biomes, but it will be capable of neither halting nor of reversing the loss. Liberalization has the effect of accelerating biodiversity loss across the board, with few exceptions. A coherent sustainability scenario is clearly the most effective at preserving biodiversity, but the variant tested here still does not halt losses in all cases. Main conclusions Current EU policies for protecting biodiversity appear to be insufficient to reverse ongoing losses. Coherent sustainability strategies are effective at conserving biodiversity, but in order to assess losses and then reverse them, measures would need to be introduced that extend beyond the steps tested in the ALARM sustainability scenario.

The socio‐economic modelling of the ALARM scenarios with GINFORS: results and analysis for selected European countries - Andrea Stocker; Ines Omann; Jill Jäger (Global Ecology and Biogeography, 2012)
Aim This paper identifies socio‐economic driving forces of biodiversity change and analyses their political and economic dynamics by modelling socio‐economic parts of three scenario storylines developed for the ALARM (assessing large‐scale risks for biodiversity with tested methods) project. In the BAMBU (business‐as‐might‐be‐usual) scenario policy decisions already made in the European Union (EU) are implemented and enforced, but no additional measures are introduced. The GRAS (growth applied strategy) scenario describes a future world orientated towards economic growth and complete deregulation. And finally, SEDG (sustainable European development goal) is a normative scenario focusing on the achievement of sustainable development. Methods The GINFORS (global inter‐industry forecasting system) model is applied to quantify the effects of different sets of policy measures representing the three scenarios. It allows investigation of the inter‐relations between socio‐economic driving forces and the state of the environment. Results The presented results for the 25 EU countries focus on the following variables: unemployment, material extraction, energy supply and CO 2 emissions. The lowest amount of unemployment is in the SEDG scenario, where it steadily decreases from 2005 to 2020. In BAMBU it falls to a level that is also below that of 2005. In GRAS, the number of unemployed people in 2020 is clearly over the value of 2005. The development of total material extraction from 2005 to 2020 is nearly stable in BAMBU, while it clearly increases in GRAS. Only in SEDG is there a reduction in resource use. None of the scenarios achieves a substantial reduction in energy use. However, the development of CO 2 emissions shows a decoupling from energy supply. For BAMBU there is a slight decline in CO 2 emissions over time, for GRAS they increase but with a slightly smaller growth rate than energy supply. In SEDG the emissions are reduced. The decoupling trends can be explained by a shift to more renewable energy sources in all scenarios, with the highest share in SEDG. Main conclusions The results indicate that a growth‐oriented policy design, such as presented in the GRAS scenario, is not compatible with the conservation of biodiversity. Only in the SEDG scenario do the policy measures support the idea of a sustainable development, but in some respects they are still not ambitious enough.

Participatory scenario development for integrated sustainability assessment - Lisa Bohunovsky; Jill Jäger; Ines Omann (Regional Environmental Change, 2011)